2014
DOI: 10.15444/gmc2014.03.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Customer Loyalty in High-Tech Internet Services

Abstract: This study aims to investigate the antecedents to customer retention and brand loyalty of Internet Service Providers (ISPs) in Thailand. Overall service quality of an ISP is determined by network quality, customer service, information support, privacy and security. The findings reveal that the positive relationships between service quality and consumers' affective evaluations (satisfaction, trust, commitment, and value) were revealed. Overall customers' satisfaction and commitment were positively associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…Service quality adalah suatu sikap dan penilaian secara menyeluruh tentang advantage dari konteks service, meskipun scope sebenarnya dari sikap ini tidaklah setuju (Robinson, 1999). Hasil studi empiris berhubungan variabel service quality terhadap variabel customer loyalty yang diteliti oleh (Albarq, 2013;Liang & Zhang, 2012;Prentice, 2013;Thaichon et al, 2012), hasil riset menemukan bahwa adanya pengaruh service quality berdampak positif dan dapat membantu meningkatkan loyalitas pelanggan.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Service quality adalah suatu sikap dan penilaian secara menyeluruh tentang advantage dari konteks service, meskipun scope sebenarnya dari sikap ini tidaklah setuju (Robinson, 1999). Hasil studi empiris berhubungan variabel service quality terhadap variabel customer loyalty yang diteliti oleh (Albarq, 2013;Liang & Zhang, 2012;Prentice, 2013;Thaichon et al, 2012), hasil riset menemukan bahwa adanya pengaruh service quality berdampak positif dan dapat membantu meningkatkan loyalitas pelanggan.…”
Section: Pendahuluanunclassified
“…Terdapat pengaruh signifikan kualitas pelayanan terhadap loyalitas pelanggan. Riset ini sejalan dengan Albarq (2013), Liang & Zhang (2012), Prentice (2013), dan Thaichon et al (2012). Kualitas Layanan yaitu "general perceptions of the company and its services by customers in terms of their relative superiority and inferiority".…”
Section: Pembahasanunclassified
“…A study of telemedicine adoption for cancer patients during the COVID-19 pandemic found that the most common patient-reported barriers to telemedicine visits included poor-quality video or audio, problems with Internet connectivity, and interruptions (Chávarri-Guerra et al, 2020). Stemming from these findings and the Thaichon et al (2012) operationalization of network quality, three dimensions of broadband service quality must be considered: consistency, persistence, and resistance to load.…”
Section: Broadband Service Qualitymentioning
confidence: 99%
“…Typically, commitment is categorised into three types: affective commitment, continuance commitment, and normative commitment (Tonder, 2016). Affective commitment is the emotional attachment to an organisation, while continuance commitment is the costs that customers associate with leaving the organisation, and normative commitment is the customer's feelings of obligation to stay with the company (Drohan, 2010;Thaichon, 2014). These three dimensions of commitment are included in this study to create a more comprehensive method to understand the relationship between commitment and loyalty (Bansod, 2011).…”
Section: Commitmentmentioning
confidence: 99%